Strategi Nafkah Petani oleh Adanya Konversi Lahan Sawah ke Lahan Kelapa Sawit (Studi Kasus Desa Padangguni Utama Kecamatan Abuki Kabupaten Konawe) - Saputra, Irpan Nuangsa; Rahmah, Nur Rahmah; Meisanti, Meisanti (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2019)
This research will be based in the background by the displacement of the rice field in Padangguni Utama Village Abuki District of Konawe Regency by conversion of rice field to palm oil field. Land conversion causes rice paddy farmers to lose some or all of their livelihoods so they have to use a variety of livelihoods strategy for surviving. The study was conducted from March to May 2017 at Padangguni Utama Village, Abuki District, Konawe District. This research uses the qualitative method with the number of key informants as much as 6 people determined by purposive and snowball. Data collection is done through the deep interview, field observation and supporting documentation data from the related institution. Data analysis was done descriptively by the triangulation method. The results found in this study indicate that land conversion occurs because farmers are attracted by large promises of compensation and promise of road improvements to be provided by the company. However, such promises are not realized as farmers hope while paddy farming land which is the main source of livelihood has been converted to oil palm. Farmers then pursued three livelihood strategies: engineering agricultural livelihoods by expanding arable land (Extensification), multiple livelihood patterns and spatial engineering.